KAREN P. HAYRAPETIAN (Words of remembrance and appreciation) - Minasyan, Edik; Grigoryan, Hovik (History and Culture, 2022)
The words of remembrance are dedicated to one of the talented historians of post-Soviet Armenia, candidate of historical sciences Karen P. Hayrapetyan. His scientific and educational activities, as well as public and state work have been mutually complementary and fruitful.